Digital Marketing, Inovasi Produk Dan Sosial Capital Pengaruhnya Terhadap Peningkatan Kinerja Pemasaran (Studi Kasus Pada UMKM Produk Koral dan Ikan Hias - Akmal Abdullah; Andi Baso Adil Natsir Baso; Ilham Ilham; Sulkifli Sulkifli (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The objective of this study is to investigate the influence of digital marketing, product innovation, and social capital on the success of marketing performance improvement. The approach employed for sampling is non-probability sampling, specifically quota sampling. This study employed a sample size of 100 respondents, selected according on the criteria of MSME Coral and Ornamental Fish Product in Makassar. The data collection approach employed in this study involves the use of a questionnaire that utilizes a Likert scale as a measurement device. Quantitative research approaches were employed to gather primary data. The data was analyzed using multiple linear regression analysis with the assistance of SPSS software. Based on the results of this study, it is observed that the p-value associated with the social capital variable and its impact on marketing performance is 0.653, which above the conventional significance level of 0.05. Additionally, the t-value obtained from the t-table is 0.451, which is lower than the critical value of 1.985. Based on the findings, the null hypothesis (H0) is accepted while the alternative hypothesis (H1) is rejected. This suggests that there is no substantial impact of Social Capital on the marketing performance of MSMEs' Coral and Ornamental Fish products in Makassar.